Peran Mata Kuliah Modul Nusantara dalam Meningkatkan Wawasan Kebhinekaan Mahasiswa melalui Kegiatan Pertukaran Mahasiswa Merdeka - Friska Yanti Br Purba; Tika Yohana Sinaga; Anggi Lastri Pinayungan (Departement of Mathematics Education, 2023)
This study aims to find out how big the role of the Nusantara Module Course is so that it has an impact on increasing student Insight into Diversity. This research uses a descriptive qualitative approach. The subjects of this study were Inbound Students at Yogyakarta State University and Surabaya State University in 2022. Data collection using the Observation and Research results showed that the Nusantara Module Course had a major role in increasing insight into the diversity of inbound students, including; First, students have new experiences and knowledge about culture and history that were previously unknown to students; Second, students are able to reflect and show how to preserve and have a sense of protecting the prevailing histories in Indonesia which are still a state tribute or museums which must be kept intact in their historical form; Third, students have strong national character and insight and high morals to match their intelligence to become young cadres of state defense who understand